From the treatment of breast cancer to the treatment of the woman with cancer: history of breast surgery and its prejudices - Depaoli, Francesca; Ciliberti, Rosagemma (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The article offers a comprehensive analysis of the historical evolution in breast cancer treatment since ancient times, when various methodologies were practiced, ranging from deliberate abstention to brutal treatments such as cauterization or amputation. Methods: The analysis was conducted through an extensive review of literature and of articles in databases such as Medline, Google Scholar, and PubMed. Results: Following the technique described by Halsted in 1894, which involved an extremely invasive procedure, advancements in scientific knowledge gradually allowed for more advanced surgical techniques that are respectful of bodily integrity. As treatments have evolved, the focus has been on increasing overall and disease-free survival. The increased understanding of tumor characteristics, adoption of multidisciplinary approaches, and societal shifts towards health have led to a significant evolution in breast cancer diagnosis and treatment. Conclusions: This transition from aggressive to more tailored therapies, including localized and systemic treatments, has improved survival rates and patient quality of life. Current research is exploring the possibility that future breast cancer therapies may even eliminate the need for breast and axillary surgeries, thus revolutionizing the therapeutic approach.